Nutrition for dummies - Rinzler, Carol Ann
You are what you eat: good nutrition is the key to a healthy weight and good health. Rinzler shows you how to manage your diet, prepare healthy foods, and cut calories by making wise food choices.
Nutrition 101: the basic facts about nutrition -- The good stuff in your food -- Training and development -- Food processing -- Food and medicine -- The part of tens.
Includes index.
Keywords: Nutrition; Dietetics; HEALTH & FITNESS; Dietetics; Nutrition